The Ecopsychological Relevance of Nathaniel Hawthorne’s Rappaccini’s Daughter for an AI-Driven World - Amalia Kurnia Devi; Novita Dewi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2025)
The ethical and environmental implications of technological advancement are frequently questioned in the age of artificial intelligence (AI) and biotechnology. We examine Rappaccini’s Daughter by American Dark Romantic Nathaniel Hawthorne to show how the short story resonates with contemporary concerns about AI and automation that may replace human connection and empathy. We employ a contextual and environmentally sensitive interpretation of the text to reveal Hawthorne’s criticisms of an over-reliance on human reason and science, which perpetuates the characters’ alienation and dehumanization. In light of concepts in ecopsychology, i.e., biophobia and alienation, the findings reveal that Rappaccini’s Daughter 1) warns against the tragic consequences of manipulating nature beyond control, and 2) explores the awkward relationship between artificial creation and environmental ethics. We conclude that unscrupulous scientific pursuits ultimately lead to ecological and psychological harm and the loss of genuine beauty. Seen as cautionary tales, 19th-century literary works such as Rappaccini’s Daughter can thus be revisited as they offer insights into how individuals today cope with ecological anxieties.